Minimum Wages and Employment in Swedish Hotels and Restaurants - Per Skedinger (The Research Institute of Industrial Economics (IUI), 2002)
This paper considers the effects of union-bargained minimum wages on transitions into and out of employment in the hotels and catering industry over the period 197999. This industry is characterised by a high fraction of unskilled labour input, high worker turnover and binding minimum wages. The empirical approach identifies workers affected by real minimum wage increases and decreases, respectively. Job separations and accessions for the treatment groups are then contrasted to the outcomes for control groups, with wages marginally above those of the treatment groups. Unlike previous studies, this paper also considers same-period transitions for same-wage workers who are unaffected by minimum wage changes. This procedure should help to control for unobserved differences between high- and low-wage workers and is made possible by the diversified minimum wage structure of the industry. According to the results, increasing minimum wages tend to be associated with non-negligible employment effects (except for teenagers during 199398). The evidence regarding decreasing minimum wages is less conclusive.
Keywords: J23; J31; J51; 330; Minimum Wages; Employment; Mindestlohn; Beschäftigung; Tourismusberufe; Schweden